Factors influence on atmospheric concentrations of beryllium-7 (7Be) in the Chernobyl zone - Batrakov Gennady Fedorovich; Kremenchutskii Dmitrii Aleksandrovich; Nazarov Aleksandr Borisovich; Kholoptsev Aleksandr Vadimovich (ООО «Олимп», 2016)
The paper presents the results of monitoring of 7Be concentration in the surface atmospheric layer of Chernobyl for the period from July 2005 to May 2010. The features of influence of factors such as rainfall, storm activity, temperature and wind speed on the concentration of the isotope were examined. It was shown that significant impact on variation of 7Be concentrations have a flux of thermal neutrons produced during thunderstorms and intensification of vertical exchange in the troposphere.
Keywords: BERYLLIUM-7 (7BE); THUNDERSTORM ACTIVITY; METEOROLOGICAL PARAMETERS; CHERNOBYL ZONE; БЕРИЛЛИЙ-7(7BE); ИНДЕКС ГРОЗОВОЙ АКТИВНОСТИ; МЕТЕОПАРАМЕТРЫ; ЧЕРНОБЫЛЬСКАЯ ЗОНА